Management of local or regional non‐nodal disease. Issue 2 (12th December 2018) - Racz, Jennifer M.; Block, Matthew S.; Baum, Christian L.; Jakub, James W.
Abstract : Some melanomas develop a striking avidity for lymphatic spread. In spite of multiple recurrences, patients can remain years without visceral metastasis. There is clearly a biologic reason for this lymphotrophic pattern of growth and dissemination, which we have yet to uncover. In‐transit metastases have widely diverse clinical presentations and can be a stubborn disease to cure. As a result, a host of treatments exist that should be tailored to the individual patient.